PERAN MINUSCA PEACEKEEPING OPERATION DALAM MENJAGA STABILITAS KEAMANAN REPUBLIK AFRIKA TENGAH 2019-2023 - Yovana, Kesi; Ananda, Fatjar Haris (Moestopo Journal of International Relations (MJIR), 2024)
This research aims to analyse the role of the United Nations Multidimensional Integrated Stabilization Mission in the Central African Republic (MINUSCA) in running the peacekeeping operation program to maintain security stability in the Central African Republic after the ceasefire 2019-2023. This research uses a descriptive qualitative method with a literature study approach that collects data from various sources such as books, journals, articles, and official reports and websites. In this research, the concepts of Role and Peacekeeping as well as the theory of the Role of International Organisations and Conflict Resolution are used as an analytical framework. The results show that MINUSCA has three main tasks in maintaining security stability in the Central African Republic, namely Protection of Civilians, Support to Political Transition, and Restoration of State Authority. Despite challenges such as violations of the peace agreement by rebel groups, limited resources, and resistance to the presence of peacekeepers, MINUSCA still plays a key role in protecting civilians, overseeing the political process, and supporting security sector reform in the country.